Adenomatous hyperplasia endocervix - Rozas Llerena, Rubén (2015)
50 cases of adenomatous hiperplasia of endocervix are reported in 500 cervical biopsy. The rate average was 47 year old. The main symptom was uterine bleeding. Predominant clinic diagnosis was fibroma, and anatomy pathologycal diagnosis were: Adenomyosis, leiomioma, atrophy endometrium, proliferative phase, secretory phase and adenomatous hiperplasia in that order. A high hormonal strogenic factor is suggested as probable etiophatogenic in postmenopause, multipara women. It is important to avoid the misdiagnosis microscopically with adenocarcinoma well differentiated since this reaction is invariably benign.